Silibinin and indocyanine green-loaded nanoparticles inhibit the growth and metastasis of mammalian breast cancer cells in vitro - Sun Hui-ping; Su Jing-han; Meng Qing-shuo; Yin Qi; Zhang Zhi-wen; Yu Hai-jun; Zhang Peng-cheng; Wang Si-ling; Li Ya-ping (Acta Pharmacologica Sinica, 2017)
Aim: To improve the therapeutic efficacy of cancer treatments, combinational therapies based on nanosized drug delivery system (NDDS) has been developed recently. In this study we designed a new NDDS loaded with an anti-metastatic drug silibinin and a photothermal agent indocyanine green (ICG), and investigated its effects on the growth and metastasis of breast cancer cells in vitro. Methods: Silibinin and ICG were self-assembled into PCL lipid nanoparticles (SIPNs). Their physical characteristics including the particle size, zeta potential, morphology and in vitro drug release were examined. 4T1 mammalian breast cancer cells were used to evaluate their cellular internalization, cytotoxicity, and their influences on wound healing, in vitro cell migration and invasion. Results: SIPNs showed a well-defined spherical shape with averaged size of 126.3±0.4 nm and zeta potential of −10.3±0.2 mV. NIR laser irradiation substantially increased the in vitro release of silibinin from the SIPNs (58.3% at the first 8 h, and 97.8% for the total release). Furthermore, NIR laser irradiation markedly increased the uptake of SIPNs into 4T1 cells. Under the NIR laser irradiation, both SIPNs and IPNs (PCL lipid nanoparticles loaded with ICG alone) caused dose-dependent ablation of 4T1 cells. The wound healing, migration and invasion experiments showed that SIPNs exposed to NIR laser irradiation exhibited dramatic in vitro anti-metastasis effects. Conclusion: SIPNs show temperature-sensitive drug release following NIR laser irradiation, which can inhibit the growth and metastasis of breast cancer cells in vitro.